Answers to the problem of death between classical and early Christian mentality - Pizzolato, Luigi Franco (Medicina e Morale, 2024)
Death constitutes a decisive problem for any mentality, but particularly for the Greek mentality, which is inclined to investigate the problems, so to speak, of ultimate meaning, of man and the world, more than to describe phenomena. And it is a fact that tragically touches everyone and that instils in everyone that fear, which comes from the impossibility of fully grasping its explanation.